PENGARUH JENIS DAN DOSIS PENGGUNAAN PUPUK KANDANG PADA SORGUM TERHADAP FASE VEGETATIF PADA PEMOTONGAN KEDUA - Agung Kusuma Wijaya (Jurnal Agrotek Tropika, 2019)
ABSTRACT Effect of Type and Dose of Manure to Sorghum on Vegetative Status in The Second Harvest. This research aims to study the effect of type and dose of manure on productivity of fresh production, number of tillers, and proportion of stems leaves of sorghum  in the second period. This research was conducted on January—Juni 2017 at Kemiling, Bandar Lampung.  The study was done based on Completely Randomized Design (CRD) split plot design (distributed plot design) with two levels of treatment that is the main treatment (main plot) and saplings plot treatment (sub plot).   The main of treatment types of manure which covers: K1 (cow dung manure); K2 (goat's dung manure); and K3 (chicken manure).  Treatment number of tillers use dose of manure which covers, R0 (0 tons/ha); R1 (15 ton/ha); R2 (20 tonnes/ha); and R3 (25 ton/ha.  Each experimental unit consists of 2x1,8 m2plot of land.  Each experimental treatment unit  is repeated three times, so there are 36 units of experiments. Obtained data were analyzed with the assumptions of variance by 5% or 1%.  Results showed that doses of manure did not significantly affect (P>0,05)  fresh production, number of tillers and proportion of stems and leaves. Use of manure type did not significantly affect (P>0,05) fresh production, number of tillers, and proportion of stems and leaves.